2001
DOI: 10.1107/s1600536801007838
|View full text |Cite
|
Sign up to set email alerts
|

cis-Bis(2,2-bipyridine)dichloronickel(II) methanol solvate

Abstract: The title complex, [NiCl2(bipy)2].CH3OH, where bipy is 2,2‐bi­pyridine (C10H8N2), consists of an Ni atom coordinated to two cis chlorides and two bidentate bi­pyridines. One mol­ecule of methanol is hydrogen bonded to one of the two inequivalent chlorides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…The Rh-N axial bond distance (2.038 (3) Å) is slightly longer than Rh-N equatorial bonds (average 2.026 (5) Å). Its may be well compared with the negligible difference between equatorial and axial M-N bonds distances seen in the analogous complexes of platinum metal group (Lahuerta et al, 1991;Kim et al, 2009;Helberg et al, 1996;Prajapati et al, 2008;Eggleston et al, 1985), but greater distortion observed in majority of transition metal complexes (Strenger et al, 2000;Fontaine, 2001;Kramer & Straehle, 1986;Sofetis et al, 2006;Figgis et al, 1985;Choudhury et al, 2006;Gao & Ng, 2010). The Rh-Cl bond distances in (I) are 2.3291 (9) (equatorial) and 2.3344 (9) Å (axial …”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The Rh-N axial bond distance (2.038 (3) Å) is slightly longer than Rh-N equatorial bonds (average 2.026 (5) Å). Its may be well compared with the negligible difference between equatorial and axial M-N bonds distances seen in the analogous complexes of platinum metal group (Lahuerta et al, 1991;Kim et al, 2009;Helberg et al, 1996;Prajapati et al, 2008;Eggleston et al, 1985), but greater distortion observed in majority of transition metal complexes (Strenger et al, 2000;Fontaine, 2001;Kramer & Straehle, 1986;Sofetis et al, 2006;Figgis et al, 1985;Choudhury et al, 2006;Gao & Ng, 2010). The Rh-Cl bond distances in (I) are 2.3291 (9) (equatorial) and 2.3344 (9) Å (axial …”
Section: Methodsmentioning
confidence: 88%
“…Data collection: CrysAlis PRO (Agilent, 2011); cell refinement: CrysAlis PRO; data reduction: CrysAlis PRO; program(s) used to solve structure: SIR92 (Altomare et al, 1994); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: Mercury (Macrae et al, 2006); software used to prepare material for publication: WinGX (Farrugia, 1999) In recent years, noble metal complexes of pyridyl ligands have received much attention because of their rich electrochemical (Rasmussen et al, 1990, photophysical (Forster & Rund, 2003 and photochemical (Arachchige et al, 2008) properties, and their potential applications in catalysis (Mbaye et al, 2003), biochemistry (Tan et al, 2005;Chifotides et al, 2004) and anticancer activity (Karidi et al, 2005). Bipyridine (bipy) is one of the most commonly used bidentate ligand of this type in the formation of wide variety of transition metal complexes with a general formula of Mn, Fe) in which X is an coordinated anionic ligand such as CN, SCN and chloride (De Munno et al, 1993;Eggleston et al, 1985;Kramer & Straehle, 1986;Al-Noaimi and Haddad, 2007;Fontaine, 2001;Choudhury et al, 2006;Gao & Ng, 2010) (Figgis et al, 1985;Sofetis et al, 2006;Andansen & Josephsen, 1971;Strenger et al, 2000;Kim et al, 2009;Prajapati et al, 2008;Helberg et al, 1996). The complex [RhCl 2 (bipy) 2 ]Cl.2H 2 O has also been obtained and crystallographycaly determined by Lahuerta et al, 1991.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the coordinating pyridyl nitrogen atoms and the nickel center, Ni1, is in the range 2.047−2.087 Å (Table S2); these distances are similar to the average Ni-N distance of 2.073−2.100 Å in cisbis(bipyridine)nickel(II) dichloride. 11 The crystal structure shows that the nickel center fits the cavity of azacalix [4](2,6)pyridine framework with a reasonable geometry and bond distances. These results are consistent with the fact that a Ni 2+ ion serves as the template for preferentially affording azacalix [4](2,6)pyridines.…”
Section: Tetrahedron Lettersmentioning
confidence: 93%
“…In the title complex, the Ni atom has a distorted octahedral coordination by four N atoms from two 5,5c-dimethyl-2,2c-bipyridine ligands and two Clanions. [ 36 ]. The pyridine rings in the title complex are slightly distorted from planarity.…”
Section: Spectroscopic Characterization Of [Ni(55c-dmbipy) 2 CL 2 ]3mentioning
confidence: 93%